Association between up‐titration of medical therapy and total hospitalizations and mortality in patients with recent worsening heart failure across the ejection fraction spectrum. (13th June 2021) - Bistola, Vasiliki; Simitsis, Panagiotis; Parissis, John; Ouwerkerk, Wouter; van Veldhuisen, Dirk J.; Cleland, John G.; Anker, Stefan D.; Samani, Nilesh J.; Metra, Marco; Zannad, Faiez; Polyzogopoulou, Eftihia; Keramida, Kalliopi; et al.
Abstract: Background: The role of neurohormonal inhibition in chronic heart failure (HF) is well established. There are limited data on the effect of up‐titration of renin–angiotensin inhibitors (RASi) and beta‐blockers (BBs) on clinical outcomes of patients with worsening HF across the left ventricular ejection fraction (LVEF) spectrum. Methods and results: We analysed data from 2345 patients from BIOSTAT‐CHF (80.9% LVEF <40%), who completed a 3‐month up‐titration period after recent worsening of HF. Patients were classified by achieved dose (% of recommended): ≥100%, 50–99%, 1–49%, and none. Recurrent event analysis using joint and shared frailty models was used to examine the association between RASi/BB dose and all‐cause and HF hospitalizations. In the 21 months following up‐titration, 512 patients died and 879 (37.5%) had ≥1 hospitalization. RASi up‐titration was associated, incrementally, with reduced risk of all‐cause hospitalization at all achieved dose levels compared to no treatment [hazard ratio (95% confidence interval): ≥100%: 0.60 (0.49–0.74), P < 0.001; 50–99%: 0.56 (0.46–0.68), P < 0.001; 1–49%: 0.71 (0.59–0.86), P < 0.001]. This association was consistent up to an LVEF of 49% ( P < 0.001), and when considering only HF hospitalizations. Up‐titration of BBs was associated with fewer all‐cause hospitalizations only when LVEF was <40% (overall P < 0.001), but with more HF hospitalizations when LVEF was ≥50%. Up‐titration of both RASi/BBs was associated with lower mortality in LVEF up to 49%. Conclusion: After recent worsening of HF, up‐titration of RASi and BBs was associated with a better prognosis in patients with LVEF ≤49%. Up‐titration of BBs was associated with a greater risk of HF hospitalization when LVEF was ≥50%.